Antioxidant Activity of Crude Protein of Xestospongia Sponge from Spermonde Sulawesi - Tahirah Hasan; Mega Sari Juane Sofiana; Apriansyah; Lucky Hartanti; Desriani Lestari; Ikha Safitri; Syarif Irwan Nurdiansyah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Xestospongia sp. is a barrel sponge belonging to the phylum porifera of the class Demospongia. This sponge abundant in coral reefs ecosystem. It is a filter feeder where the filtering of nutrients available in the environment occurs in the pores along the body. Various microorganisms in the seawater were exposed to sponges, so that they can produce various biological activities. This study aims to determine the antioxidant activity of crude protein from sponge Xestospongia sp from Spermonde waters of Sulawesi Island. The protein of the sponge was extracted using ammonium sulfate. Then, the protein was determined by the Lowry method in each fraction. Furthermore, the antioxidant activity was carried out by the DPPH method. The crude protein extracts in various fractions produced intermediate antioxidant activity produced from each fraction. They are fraction 1 (0-30%) of 81.31 ppm, fraction 2 (30-60%) was 180.22 ppm, and fraction 3 (60–90%) was 93.97 ppm, while crude protein was 128.33 ppm.The ascorbic acid as a positive control has antioxidant 2.98 ppm.